Soil chronosequence derived from landslides on the upper reach of Minjiang River, western China - He, Jun-bo; Wu, Yan-hong; Bing, Hai-jian; Zhu, He; Zhou, Jun (Journal of mountain science, 2023)
Soil chronosequences derived from landslides with certain time series are the great avenue to elevate our understanding on the processes of pedogenesis, nutrient dynamics, and ecosystem evolution. However, the construction of reliable soil chronosequence from historical landslides remains intricate. Here, we presented a 22,000-year soil chronosequence from multiple landslides on the upper reach of Minjiang River, western China. The variation in a variety of pedogenesis indices and soil nutrients verified the reliability of the chronosequence. The silica-alumina ratio and silica sesquioxide ratio decreased significantly with soil age. This reflected the enrichment of Al/Fe/Ti oxides but the depletion of Si oxides with the soil development. Meanwhile, the values of the Chemical Index of Weathering and the Chemical Index of Alteration increased significantly with soil age, especially from 5 to 89 years. These variations were attributed to the soil weathering, which led to the destruction of soil minerals with the rapid loss of most of cations (e.g., K, Na, Ca, and Mg) during the soil development. The concentrations of carbon and nitrogen in topsoil increased with soil age, and the carbon accumulation rate slowed significantly from 5,500 to 22,000 years. The total phosphorus concentrations decreased with soil age, suggesting the gradual loss of soil phosphorus with soil development. The results indicate that the landslide chronosequence established on the upper reach of Minjiang River is reliable and delineates a long-term soil development process, which will provide a great platform for further improvement of biogeochemical theories and understanding sustainable vegetation restoration.